Evaluation of Downstream Processing, Extraction, and Quantification Strategies for Single Cell Oil Produced by the Oleaginous Yeasts Saitozyma podzolica DSM 27192 and Apiotrichum porosum DSM 27194 - Gorte, Olga; Hollenbach, Rebecca; Papachristou, Ioannis; Steinweg, Christian; Silve, Aude; Frey, Wolfgang; Syldatk, Christoph; Ochsenreither, Katrin (Frontiers in Bioengineering and Biotechnology, 2020)
Single cell oil (SCO) produced by oleaginous yeasts is considered as a sustainable source for biodiesel and oleochemicals since its production does not compete with food or feed and high yields can be obtained from a wide variety of carbon sources. Downstream processing is still costly preventing the broader application of SCO. Direct transesterification of freeze-dried biomass is widely used for analytical purposes and for biodiesel production but it is energy intensive and, therefore, expensive. Additionally, only fatty acid esters are produced limiting the subsequent applications. The harsh conditions applied during direct esterification might also damage high-value polyunsaturated fatty acids. Unfortunately, universal downstream strategies for all yeast species do not exist and have to be developed for each yeast species due to differences in cell wall composition. Therefore, the aim of this study was to evaluate three industrially relevant cell disruption methods combined with three extraction systems for the SCO extraction of two novel, unconventional oleaginous yeasts, Saitozyma podzolica DSM 27192 and Apiotrichum porosum DSM 27194, regarding cell disruption efficiency, lipid yield and oil quality. Bead milling and high pressure homogenization were effective cell disruption methods in contrast to sonification. By combining high pressure homogenization (95 % cell disruption efficiency) with ethanol-hexane-extraction 46.9 ± 4.4 % lipid/ CDW of S. podzolica DSM 27192 were obtained which was 2.7 times higher than with the least suitable combination (ultrasound + Folch). A. porosum DSM 27194 was less affected by cell disruption attempts. Here, the highest disruption efficiency was 74 % after bead milling and the most efficient lipid recovery resulted from direct acidic transesterification (27.2 ± 0.5 % fatty acid methyl esters/ CDW) after freeze drying. The study clearly indicates cell disruption as the decisive step for SCO extraction. At disruption efficiencies of > 90 %, lipids can be extracted at high yields, whereas at lower cell disruption efficiencies, considerable amounts of lipids will not be accessible for extraction regardless of the solvents used. Furthermore, it was shown that hexane-ethanol which is commonly used for extraction of algal lipids is also highly efficient for yeasts.